A shear-thinning hydrogel that extends in vivo bioactivity of FGF2. (December 2016) - Ding, Xiaochu; Gao, Jin; Wang, Zhouguang; Awada, Hassan; Wang, Yadong
Abstract: We designed and tested a versatile hydrogel for tissue regeneration by preserving the bioactivity of growth factors. The shear-thinning gel self-assembles within 1 min from heparin and Laponite-a silicate nanoparticle, thus the name HELP gel. By not covalently modifying heparin, it should retain its natural affinity towards many proteins anchored in the extracellular matrix. In principle, HELP gel can bind any heparin-binding growth factor; we use fibroblast growth factor-2 (FGF2) in this study to demonstrate its utility. Heparin in the gel protects FGF2 from proteolytic degradation and allows it to be released over time with preserved bioactivity. FGF2 released from subcutaneously injected gel induces strong angiogenesis in a mouse model. The hydrogel degrades completely in vivo in 8 weeks with or without growth factors, eliciting mild inflammatory response but having little impacts on the surrounding tissue. The ease of preparation and scale-up makes this protein delivery platform attractive for clinical translation.